ЗА ЛЕКСИКАТА НА ХИМНОГРАФСКИТЕ ТЕКСТОВИ ОД МАКЕДОНСКА РЕДАКЦИЈА∗ (Filološke pripombe, 2019)
Subject of interest of our paper is the hymn graphic lexis in the triodes and in the menology, treated for the purposes for creating the Dictionary of the Macedonian Recension of Church Slavonic. The hymn graphic texts, with their specific characteristics, enrich the knowledge on the Church Slavonic lexical fund, as a part of this Dictionary. The style of the hymn graphic texts requires specific selection of certain phonological, morphological and above all, lexical and word formation units, presence of archaic and updated lexis, words from the vernacular, as well as updates from the field of word formation.